The Role Of European Culture In Shaping Ahmad Donish’s Worldview - Bozorov Shukhrat Salaydinovich (Global Scientific Publishing, 2025)
This article analyzes the views of the 19th-century Bukharan thinker Ahmad Donish- who lived and worked during a period of socio-political crisis in the Emirate of Bukhara - regarding European culture, science, and enlightenment. The author examines, on a scholarly basis, Donish’s real-life observations made during his journey to Russia, his reflections on European progress, his comparative assessment of Eastern and Western civilizations, and his proposals for reforming Bukharan society
Keywords: Ahmad Donish; European culture; Emirate of Bukhara